Ovarian cancer with pleural and lung metastasis in Dr. Soetomo Hospital, Surabaya, Indonesia, in 2014-2015 - Fitria Khusnul Khotimah; Anna Febriani; Pungky Mulawardhana (Universitas Airlangga, 2018)
Objectives: To know the characteristics of ovarian cancer patients with pleural and lung metastasis, and survival rates of ovarian cancer patients with pleural and lung metastasis in Dr. Soetomo Hospital Surabaya in 2014-2015.Materials & Methods: This was a descriptive observational study using secondary data from medical records in dr. Soetomo Hospital, Surabaya, Indonesia, in 2014 and 2015Results: Number of new patients of ovarian cancer in dr. Soe-tomo, Hospital, Surabaya in 2014 was 170 patients (14%) and 122 patients (12%) in 2015. Ovarian cancer patients most often came at the stage IIIC (33.38%) with the most histopathological type was epithelial ovarian cancer. There were 5 patients with ovarian cancer with pleural metastasis and 7 patients with lung metastasis. Pleural metastasis was 80% diagnosed at the time of ovarian cancer’s diagnosis, whereas 57.15% of lung metastasis were diag-nosed >12 months after the ovarian cancer’s diagnosis. Pleural metastasis was established by pleural fluid cytology, while lung metastasis with radiological features and/or biopsies. The most common feature of lung metastasis was nodal (71.42%). Ascites was found in 80% of ovarian cancer with pleural metastasis, but only 42.86% in lung metastasis. In 2 patients receiving NAC chemotherapy and continued by interval debulking, both had negative residues. Median survival rate in ovarian cancer with pleural metastasis was 7 months, whereas in lung metastasis was 12 months.Conclusions: Number of new patients of ovarian cancer in 2014-2015 in dr. Soetomo Hospital was on rising and was the second largest number of visits after cervical cancer. In 2014-2015, there were 5 patients with ovarian cancer and pleural metastasis and 7 patients with ovarian cancer patients and lung metastasis. Median survival rate in ovarian cancer with pleural metastasis was 7 months, whereas in lung metastasis it was 12 months.